Religious Denomination, Religiosity, Religious Attendance, and Cancer Prevention. A Systematic Review - Kretzler B; König HH; Brandt L; Weiss HR; Hajek A (Dove Medical Press, 2022)
Benedikt Kretzler, Hans-Helmut König, Linéa Brandt, Helene Rabea Weiss, André Hajek Department of Health Economics and Health Services Research, University Medical Center Hamburg-Eppendorf, Hamburg, GermanyCorrespondence: Benedikt KretzlerDepartment of Health Economics and Health Services Research, University Medical Center Hamburg-Eppendorf, Martinistraße 52, Hamburg, 20251, GermanyTel +49 40 741 024 161Fax +49 40 741 040 261Email b.kretzler.ext@uke.deAbstract: Recent research highlighted the influence of religion among health outcomes. To the best of our knowledge, there is no systematic review that summarizes the evidence on the relationship between religious factors and the utilization of cancer screenings. Therefore, this article aims to list the findings about the influence of religious denominations, the importance of religion in one's life, and religious practices, such as church attendance on the utilization of cancer screenings. PubMed, PsycInfo and CINAHL were searched using a predefined algorithm in June 2020. We included observational studies that examined the association between religion and cancer screening use and employed appropriate items to quantify these key variables. Study selection, data extraction and quality assessment were performed independently by two reviewers. We detected n=27 studies that fulfilled the inclusion criteria. Hereby, n=16 used data from the United States. Most of the studies that were included in our review found a positive association between religious attendance and cancer screening utilization. There was mixed evidence concerning religious denomination as well as religiosity and use of cancer screenings. The studies suggest that religious factors are related to the utilization of cancer screenings. The findings of this systematic review may be helpful to resolve the underuse of cancer screenings by revealing at-risk-groups.Keywords: spirituality, religiosity, cancer screening, preventive medicine, religious denomination, systematic review